Sexual Dysfunction Related to Psychotropic Drugs: A Critical Review – Part I: Antidepressants - La Torre, A.; Giupponi, G.; Duffy, D.; Conca, A. (Pharmacopsychiatry, 2013)
Sexual dysfunction is a potential side effect of antidepressant drugs: this article presents a critical review of the current literature. Although many studies have been published on this subject, only some have used a validated sexual function rating scale and most lacked either a baseline or placebo control or both. In addition, many of the studies on sexual dysfunction associated with antidepressants are limited by other methodological flaws. However, there is consistent evidence to suggest that antidepressant medication adversely affects one or more of the 3 phases of sexual response (desire, arousal and orgasm). Antidepressants with strong serotonergic properties have the highest rate of sexual side effects. Clinicians must be aware of drug-induced sexual dysfunction, since its presence can have important consequences on clinical management and compliance.
Keywords: antidepressant drugs; sexual dysfunction; sexual side effects; treatment-emergent sexual dysfunction